Distribución geográfica y ecológica de la nutria de río neotropical (Lontra longicaudis) en Michoacán, México - Monterrubioâ€“Rico, Tiberio C.; Charreâ€“Medellín, Juan F. (THERYA, 2014)
Introduction: Considering the general deterioration of Michoacán rivers, increased poaching, the failure to enforce relevant laws in the last 10 years, and the absence of a detailed assessment of the current status of the river otter (Lontra longicaudus) in the state of Michoacán, our main goal was to collect and analyze all available historical and recent evidence for the occurrence of the river otter in this state. The study focused on three regions for which field recordings were obtained during the period 2005 to 2012. Our second objective was to analyze the ecological conditions associated with these recent records. This information is especially important because the species is protected in Michoacán, and it is an indicator of the environmental quality of water bodies. Methodology: Historical records of otters in Michoacán were reviewed to establish their reliability and age. The search included scientific papers, theses, and data bases of scientific collections available on line. The current presence of river otters in the state was further documented by diurnal transects along rivers and streams in which visual records, footprint tracks, feces, burrows, latrines, or skulls were obtained. The records were then projected on maps in order to analyze them in the context of biogeographic regions, watersheds, vegetation-types, climate, cities, and rivers. Results: The presence of river otters in Michoacán was documented by only 10 historical records (Fig. 1, Table 1). Our field work generated 90 records in 17 localities (Fig. 2, Table 1). The records were found in four watersheds. The type of vegetation that is associated with the largest number of records was the tropical deciduous forest (n = 47, 52%), which is characterized by average temperatures between 21 and 28 â°C and annual rainfall between 700 and 1,300 mm. Discussion and conclusions: Our results represent the most recent records for L. longicaudus for the state of Michoacán, and perhaps for any other state in central-western Mexico. The observed distribution of the river otter confirms its presence in at least three major biogeographic regions of Michoacán, namely Balsas, Sierra Madre del Sur, and Pacific Coast. All the data obtained during the study associate this species with perennial streams and where permanent pools remain during the dry season (Fig. 1). This area may be an important refuge for this species because a hydrological network is spread over environmental heterogeneity encompassing temperate forests in the Sierra Madre del Sur and the Eje Neovolcanico to tropical deciduous forests along the Balsas River and the Pacific coast. In the future, it will be important to document if this otter occurs in the Zicuirán-Infiernillo Biosphere Reserve which seems to have the potential for connectivity with rivers in the state of Guerrero. This would make the Michoacán otters of considerable importance for conservation programs on a regional level. Key words: climatic profile, Balsas, Mustelidae, skull, water dog.